Inference in media space. The case of IBM Software Executive Briefing Center - Rome - Toni Marino (Ocula, 2014)
In our paper we apply Peirce's model of Arguments (Statistical Deduction, Probabilistic Deduction, Induction and Abduction) to a communication process where negotiating sense and meanings is emphasized. We selected a communication space where everything is planned as a medium of sense (video terminals, screens, lights, etc.) namely the IBM Software Executive Briefing Center in Italy, a workplace used to exchange views, negotiate or transact. It is based in Rome in the same building as the International Development Laboratory of the IBM Software Group. The Software Center is the place where IBM welcomes its potential customers and has the opportunity to show them its technology and offer solutions. This paper focuses on "media space" in the Center which is structured by the seller according to his/her idea of the buyer's interpretive process. This paper analyzes the roles of visual codes in the allocation of functions. It also looks into the relation between the symbolism of the company with its marketing, past history and media space in order to define the buyer's typology of inference (deduction, induction or abduction) in relation to the communication strategy of the media space design. The research is conducted directly in the field by interviewing the Manager of the IBM Center as well as asking people who use it to fill in an anonymous questionnaire, which analyses both the media space and the plan of the building.